Active restoration facilitates bird community recovery in an Afrotropical rainforest. (August 2016) - Latja, Pirita; Valtonen, Anu; Malinga, Geoffrey M.; Roininen, Heikki
Abstract: Active restoration of rainforests is essential in enhancing the recovery of biodiversity in many tropical regions suffering from deforestation. However, the value of actively restored rainforests for birds is still relatively poorly understood because of the short history of active restoration programs. Here, we studied the recovery of bird communities in Kibale National Park, Uganda. We sampled birds along a restoration gradient consisting of six restoration areas (3–16 years old) and used five primary forests as reference areas. We found that bird community compositions changed in an orderly fashion along the restoration gradient. The abundance of arboreal insectivore frugivores and forest specialists increased, while that of foliage-gleaning insectivores, granivores and forest visitors decreased towards older sites. The similarity of the bird communities of the restored forests to those of the nearby primary forests increased linearly with time. If this recovery rate is extrapolated to the future, the bird communities could reach a pre-disturbance state after only approximately 20 years of active restoration. However, previous studies have shown that recovery is typically a non-linear process, and the time needed for bird communities to recover is more likely longer than this. Nevertheless, our study provides evidence that bird communities benefit from active rainforest restoration after human-induced deforestation. Highlights: Following restoration, the community composition of birds changed. Forest specialists and frugivores increased. Forest visitors, foliage-gleaning insectivores and granivores decreased. The most sensitive forest birds did not yet return to oldest restored areas. Bird communities benefit from active restoration of rainforests after disturbance.